Post-hysterectomy rare collision vulva tumor with long-term human papilloma virus infection composed of squamous cell carcinoma of the labia major and adenosquamous carcinoma of bartholin gland: A case report. Issue 39 (September 2019) - Yang, Fan; Li, HongYi; Qi, Xiaorong; Bian, Ce
Abstract: Rationale: Post-hysterectomy collision tumors of the vulva has rarely been reported. Though long-term HPV infection may induce vulva tumor, but the relationship between HPV infection and collision vulva tumor is not clear. And there are no clear rules of the post-hysterectomy cancer surveillance for human papilloma virus (HPV) long-term infections. So here we first report a case of post-hysterectomy rare collision vulva tumor with long-term HPV infection composed of squamous cell carcinoma of the labia major and adenosquamous carcinoma of bartholin gland and hope to bring new direction to our future research. Patient concerns: A 48-year-old woman with long-term HPV infection, 3 years after hysterectomy, gravida 3, para 2, was admitted to our hospital with complaints of a 4-month history of an itching vulva ulceration. An anabrosis was located on the surface of the solid mass of the bartholin gland at the posterior part of the right labium and the right inguinal lymph nodes were palpable. Result of the incisional biopsy of the ulcer area at local hospital was atypical squamous cells couldn't exclude high-grade squamous intraepithelial lesion (ASC-H). Subsequently more authoritative pathological consultation results suggested squamous cell carcinoma of the vulva. Diagnoses: Post-hysterectomy collision vulva tumor with long-term HPV infection composed of squamous cell carcinoma of the labia major and adenosquamous carcinoma of bartholin gland. Interventions: The extensive excision of the vulva, bilateral inguinal lymph nodes dissection, and local skin flap transposition surgeon was done to this patient. The final certificate diagnosis was: vulvar tumor T1bM0N0 composed of squamous cell carcinoma of the labia major and adenosquamous carcinoma of bartholin gland; HPV infection; post hysterectomy, and bilateral salpingectomy. Outcomes: The patient recovered well after surgery, and consequently received 6 courses of TC (paclitaxel + carboplatin) chemotherapy, and 9 months and 13 days followed up. So far patient recorded as complete response (CR). Lessons: Collision vulva tumor occurred post-hysterectomy is extremely rare. It is most likely related to long-term HPV infection, which suggests us should to modify the manner of the post-hysterectomy cancer surveillance for HPV long-term infections. For patients with high-risk HPV infection, even if the cytology results are negative, we may should perform colposcopy and vulva biopsy more positively to prevent the disease from progressing into cancer. And the pathogenesis of relationship between HPV infection and collision vulva tumor is still need further investigation.